KONSEP EPIDEMIOLOGI TERJADINYA PENYAKIT TUBERKULOSIS - Putra Apriadi Siregar; Junaisa Intan Farashati, Azzahra Chandra Syafira, Dea Febrina (CV. ADIBA AISHA AMIRA, 2024)
Tuberculosis is a significant global health problem. This disease is caused by an infection with the Mycobacterium tuberculosis bacteria which spreads through the air when an infected person coughs, sneezes or talks. This study used an observational research design using a questionnaire distributed to research subjects. The research subjects consisted of individuals who had been diagnosed with tuberculosis and individuals who had not been diagnosed but had significant risk factors. The questionnaire was designed to collect information about contact history with TB sufferers, daily living habits, and other relevant risk factors. As many as 15.8% of the respondents were male and 84.1% were female. Most respondents are students / students. Observations of symptoms that appear are coughing up phlegm in the last one month and are diseases that originate from the surrounding environment. One way of transmission of pulmonary TB is from airborne bacteria, cough droplets of people with pulmonary TB and intensity of contact with people with pulmonary TB. As many as 96.4% of respondents live in a well-ventilated house and use a waterproof type of floor. As many as 22 respondents were heavy smokers who spent one pack per day. There were 2 respondents who had less nutritional status. Of the 252 respondents, 5 respondents were suspected of having pulmonary tuberculosis. Among the 5 suspected pulmonary tuberculosis respondents, there were no new cases of pulmonary tuberculosis